2020
DOI: 10.2147/dddt.s244516
|View full text |Cite
|
Sign up to set email alerts
|

<p>High ACTN1 Is Associated with Poor Prognosis, and ACTN1 Silencing Suppresses Cell Proliferation and Metastasis in Oral Squamous Cell Carcinoma</p>

Abstract: Oral squamous cell carcinoma (OSCC) is a common malignancy of the oral cavity. As the survival rate of OSCC patients is low, it is crucial to explore new markers and therapeutic targets for early diagnosis of the disease. A high level of actinin alpha 1 (ACTN1) in patients could serve as an independent prognostic factor of acute myeloid leukemia. However, the role of ACTN1 in OSCC remains unclear. In the present study, we aimed to investigate the role of ACTN1 in OSCC. Methods: ACTN1 protein levels in tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…ACTN1 has been proved to be associated with the poor prognosis in breast cancer, oral squamous cell carcinoma, and acute lymphoblastic leukemia [26][27][28]. Targeting ACTN1 by Oroxylin A could remodel stromal microenvironment and restrain breast cancer metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…ACTN1 has been proved to be associated with the poor prognosis in breast cancer, oral squamous cell carcinoma, and acute lymphoblastic leukemia [26][27][28]. Targeting ACTN1 by Oroxylin A could remodel stromal microenvironment and restrain breast cancer metastasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that CALU could be used as a potential serum biomarker for glioblastoma through a significant analysis of the microarray. ACTN1, a gene related to the microenvironment, shows prognostic value in patients with malignant glioma [22].…”
Section: Discussionmentioning
confidence: 99%
“…ACTN1 has been reported to show up-regulation within BC, which participates in cancer progression by inducing partial EMT [16]. Similarly, the aberrant expression of ACTN1 has been observed in oral, colon, hepatocellular carcinoma, acute myeloid leukemia, and lung adenocarcinoma, contributing to tumor oncogenesis and metastasis by diverse signaling pathways such as Hippo signaling and FAK/Src/ JAK2/STAT3 signaling [16][17][18][19][20][21][22][23]. These results indicate that ACTN1 may participate in tumor occurrence and development.…”
Section: Introductionmentioning
confidence: 83%